Perceived Value pada Customer Loyalty Peran Mediasi Customer Engagement: (Studi Kasus Konsumen Trika Media Internet Access) - Meryawan, I Wayan; Suryawan, Tjokorda Gde Agung Wijaya Kesuma; Handayani, Made Mulia (Universitas Pendidikan Ganesha, 2022)
The Covid pandemic has changed the pattern of people's life habits, one of the impacts felt is that the operational needs of the office work industry, schools and so on have shifted during the pandemic. One of the impacts that arises is the need for an internet connection network that supports online operational activities. This need raises opportunities for business actors and competition and competition to win the hearts of new people and old consumers to continue using the internet network services offered by the company. Based on the results of previous studies, it is strengthened that by paying attention to and increasing the existence of perceived value and the existence of customer engagement will have a strong influence on customer loyalty. The purpose of this study is to determine the influence of perceived value on customer engagement and customer loyalty, the next purpose is to determine the influence of perceived value on customer loyalty through customer engagement, especially the picture related to consumer loyalty of internet network users of the global media network. The research uses a quantitative method approach, the method of determining the number of samples using the slovin approach with a total sample of 280 consumers. The data collection method is carried out by observation techniques, interviews and the distribution of research questionnaires. Data analysis was carried out using SEM-PLS data processing software with descriptive analysis stages, inferential analysis and evaluation of the goodness of fit PLS models. The results showed that perceived value has no influence on customer loyalty, perceived value has a positive effect on customer enagement and customer engagement has a positive and significant effect on customer loyalty. Customer enagement has a mediation role full of perceived value towards customer loyalty.